Upaya Peningkatan Pengetahuan dan Sikap Remaja Putri Tentang Keputihan Melalui Pendidikan Kesehatan dengan Media Komik Elektronik dan Leaflet di SMA N 3 dan SMA N 9 Bengkulu Selatan: Efforts to Increase Knowledge And Attitudes of Young Women About Leucorrhoea Through Health Education with Electronic Comics and Leaflets at SMA N 3 and SMA N 9 South Bengkulu - Nova Magrita; Sunartono Sunartono; Fitriani Mediastuti (Journal of Health, 2024)
60% at the age of 15-22 years and 40% at the age of 23-45 years. According to data from the 2014 Indonesian Youth Reproductive Health Survey (SKRRI), women aged 15-24 years are prone to leucorrhoea. Analyzing the effect of health education through electronic comics and leaflets to increase the knowledge and attitudes of young women about leucorrhoea at SMAN 3 and SMAN 9 South Bengkulu. Quasi-experimental research with a pre-test-post-test design with a control group. The population of class XI students was 65 people at SMAN 3 and 90 people at SMAN 9 Bengkulu Selatan, using a purposive sampling method, obtained 41 respondents in the experimental group and 41 respondents in the control group. The results of the independent samples t-test show a p value of 0.008 meaning there is a difference in the average knowledge of the experimental and control groups meaning that there is an increase in the knowledge of young women about leucorrhoea after the intervention. For the attitude variable, the p value is 0.000. So there is a difference in the average attitudes of the experimental and control groups, meaning there is an increase in the attitudes of young women about leucorrhoea after the intervention. Electronic comic media and leaflets have an effect on increasing the knowledge and attitudes of young women about leucorrhoea at SMAN 3 and SMAN 9 South Bengkulu.